Perception of Ideal Breast: An Analysis of Symmetry, Size, and Shape Preferences in Turkish Population - Demiröz, Anıl; Dağhan, Başak; Yıldız Değer, Tuğba Feryal; Türkmen, Arif (Cerrahpaşa Medical Journal, 2021)
Objective: Breast is one of the secondary sex characters defining gender. It would be an appropriate approach for breast surgeons to evaluate the breast aesthetically when performing aesthetic and reconstructive breast procedures. Methods: Four different women with different breast sizes and shapes were selected. A questionnaire form was prepared with the photos taken from the front and right obliques of these four different women. The participants were asked to evaluate the symmetry, shape, and size of the breasts by looking at the photos and to determine and interpret the attractiveness score. Results: The participants were 430 men and 570 women. The B cup breast received the highest attractiveness score among the models in all the groups. Sagging has been the most commented and criticized parameter. Conclusion: In this study, we aimed to evaluate the aesthetic perspective of breast in our society and believe that it is beneficial in terms of understanding the patient’s expectations, guiding her correctly, and improving what we can do as surgeons. Cite this article as: Demiröz A, Dağhan B, Yıldız Değer TF, Türkmen A, Perception of Ideal Breast: An Analysis of Symmetry, Size, and Shape Preferences in Turkish Population. Cerrahpaşa Med J 2021; 45(1): 10-15.